Judicial oversight and the impact of laws to prevent liability - Median Jamal Al Mahasneh,; Mohamad Baraa Basel Abuanzeh, (Technium Social Sciences Journal, 2020)
The authority based on martial law or the state of emergency is accustomed to issuing legislation that works to prevent the judiciary from considering its actions that are in implementation of the customary law, and that is either during the establishment of exceptional circumstances or after its expiry meaning that it prevents individuals from resorting to the judiciary to challenge their exceptional authority Authorized to it according to the texts governing the exceptional circumstances (). The most dangerous thing that the legislative or executive authority usually does regarding a state of emergency is what it issues from laws or instructions called the laws of inclusive (laws of lifting responsibility) even though the correctness of its name in estimating some of them should be the laws of exemptions from implications (). This is because this immunization according to these laws will inevitably lead to the inability of any victim to resort to the judiciary, in the event that those who implement martial law or the state of emergency exceed their competences entrusted to them under exceptional circumstances. The Raising the Liability Law or the Implications Law is defined as legislation whose purpose is to legitimize actions that were at the time of their unlawful act, and to exempt the persons who are subject to them from the responsibility of assaulting the law, and this is what Jordan and other countries followed like France and Egypt, and that was in times of declaring martial law and a state Emergency. The methods of immunization vary and its extent varies, it may be partially preventing the appeal of cancellation or requesting the suspension of the implementation of the administrative decision only, so individuals are permitted to even seek compensation for the damage caused by the immune decision, and it may be totally, thus giving the administrative decision total immunity, whether in terms of cancellation or suspension of execution or Compensation, and it may be an absolute immunization, as it stipulates that the decision may not be appealed in any way of appeal before any judicial or administrative authority, and the immunization may be proportional, that is, with regard to preventing the appeal of the decision before the judiciary with the assignment of jurisdiction in relation to it to an administrative authority or committee, In terms of the immunization tool, it may be either by a law issued by the legislative authority, and this is the overwhelming majority, and it may be inferior to the law, such as regular systems such as customary management instructions in Jordan . In this paper, I will discuss the position of the judiciary in Jordan and the comparative judiciary regarding these legislations. To determine the impact of these laws on the right of individuals to seek legal redress when they are harmed through two topics: